Preparation of Payus Fish Protein Isolate (Elops hawaiensis) with Different pH Methods - Fatimah, Fanny Yulianti; Haryati, Sakinah; Aditia, Rifki Prayoga (Agrikan Jurnal Agribisnis Perikanan, 2024)
This research will be conducted in October-November 2023. The manufacture of protein isolates will be carried out at the Fisheries Product Processing Technology Laboratory, Department of Fisheries, Faculty of Agriculture, Sultan Ageng Tirtayasa University. Proximate and amino acid tests at the Integrated Laboratory, Bogor Agricultural University. Research on making payus fish protein isolate (Elops hawaiensis) with different pH methods has 2 stages, namely, preparation of raw materials and making payus fish protein isolate. Making payus fish protein isolate (Elops hawaiensis) with different pH methods is best at pH protein solubility pH 11. The resulting characteristic is a yield of 12.03%. Payus fish protein isolate has physical characteristics of functional properties of kamba density 0.65 g/mL, gel formation 2.5%, emulsion capacity 2.47 g/mL, low emulsion stability, oil absorption 1.20 g/mL, and water absorption 2.60 g/mL. The best chemical characteristics of payus fish protein isolate consist of water content of 21.59% (bb), ash content of 2.43% (bk), fat content of 8.78% (bk), protein content of 92.34% (bk), and carbohydrate content of 3.74% (bk). The resulting payus fish protein isolate has essential amino acid components that are quite complete so that it is categorized as a good food rich in nutritional sources. Payus fish protein isolate also contains aromatic amino acids, hydrophobic amino acids, and hydrophilic amino acids, which have the potential as antioxidants and payus fish protein isolate in studies that meet Food and Agriculture Organization standards.